Physiologic determinants of exercise capacity in patients with different types of right-sided regurgitant lesions: Ebstein's malformation with tricuspid regurgitation and repaired tetralogy of Fallot with pulmonary regurgitation. (15th February 2016) - Chen, S.S.M.; Dimopoulos, K.; Sheehan, F.H.; Gatzoulis, M.A.; Kilner, P.J.
Abstract: Background: Exercise capacity relates to right ventricular (RV) volume overload in congenital heart disease and may improve after surgery. We herewith investigate the relation between exercise capacity, cardiac index, and RV volume overload due to tricuspid regurgitation (TR) in Ebstein's malformation and pulmonary regurgitation (PR) after repair of tetralogy of Fallot (rToF). Methods: We measured cardiac index and tricuspid/pulmonary regurgitant fraction by cardiovascular magnetic resonance in patients with Ebstein's malformation (n = 40) or rTOF (n = 53) with at least moderate TR/PR and 24 healthy controls. Exercise tolerance was determined by peak oxygen consumption (peak VO2 ) during cardiopulmonary exercise testing. Results: TR and PR fraction were similar in Ebstein and rTOF patients (43 ± 17% versus 39 ± 12%, respectively). Cardiac index was reduced in Ebstein (2.7 ± 0.6 L/min/m 2 compared to controls 3.5 ± 0.9 L/min/m 2, p < 0.001) but not in rToF patients (3.2 ± 0.5 L/min/m 2 ). Multiple regression analysis revealed a significant correlation between peak VO2 and cardiac index in Ebstein. Furthermore, peak VO2 correlated with peak heart rate in both groups but not with regurgitation fraction. Conclusions: Despite comparable amounts of regurgitation from a right sided heart valve in patients with Ebstein and rToF, reduction of cardiac index was observed only in the former group. Greater physiologic complexity and adverse ventricular interaction with chronotropic incompetence in Ebstein's malformation may account for this.